SPREADING PARASITOSES OF GOATS’ GASTRO-INTESTINAL TRACT ON FARMS OF POLTAVA REGION - Prima, O. B.; Dmytrenko, N. I. (Scientific Progress & Innovations, 2021)
Parasitoses of goats’ gastrointestinal tract are widespread throughout the world, including Ukraine, and they cause significant economic damage to farms. Goats of all ages are infected with the causative agents of infestations and they often form parasitocenoses, which are in complex relationship with the host’s body. The most common among parasioses of goats’ gastrointestinal tract are helminthiases (moniesiosis, strongylidosis of the digestive organs, trichurosis, strongyloidosis, fasciolosis) and protozoases (eimeriosis). The aim of the research was to investigate the spreading and peculiarities of the course of goats’ gastrointestinal tract parasitoses on the farms of Poltava region. The study was conducted in the Laboratory of the Department of Parasitology and Ichthyopathology of S. Z. Gzhytsky Lviv National University of Veterinary Medicine and Biotechnologies and on individual peasant farms of Poltava region. The composition of pathogens parasitizing in the gastrointestinal tract of goats, the degree of their infecting and the peculiarities of parasitoses’ development were determined. According to the results of the research it has been established that the average prevalence of goats’ infestation by pathogens of gastrointestinal parasitoses in Poltava region made 62.96 %. Parasitic fauna of goats is represented by the causative agents of stronigilidoses (EI - 45.32 %), trichurosis (28.76 %), eimeriosis (24.40 %), strongyloidosis (10.89 %) and moniesiosis (6.97%). It has been determined that parasitoses of goats’ gastrointestinal tract more often occur in the form of mixed invasions, where in 71.97 % of cases the simultaneous parasitizing of two to four pathogens was detected. A total of 11 species of mixed invasions of goats’ gastrointestinal tract were identified, of which 6 combinations were two-component, 4 combinations were three-component and 1 combination was four-component. Two-component mixed invasions were the most widespread, which made 83.65 % of the total number of goats suffering from parasitoses. Three-component and four-component mixed invasions accounted for a smaller share – 14.9 and 1.45 %, respectively. The obtained data on the parasitic fauna of goats and the peculiarities of the invasions’ development will increase the effectiveness of measures to control and prevent them.